Stability and control of aircraft systems introduction to classical feedback control - Langton, Roy (Aerospace series, 2006)
In the current climate of increasing complexity and functional integration in all areas of engineering and technology, stability and control are becoming essential ingredients of engineering knowledge. Many of today's products contain multiple engineering technologies, and what were once simple mechanical, hydraulic or pneumatic products now contain integrated electronics and sensors. Control theory reduces these widely varied technical components into their important dynamic characteristics, expressed as transfer functions, from which the subtleties of dynamic behaviours can be analyzed and understood. Stability and Control of Aircraft Systems is an easy-to-read and understand text that describes control theory using minimal mathematics. It focuses on simple rules, tools and methods for the analysis and testing of feedback control systems using real systems engineering design and development examples. * Clarifies the design and development of feedback control systems * Communicates the theory in an accessible manner that does not require the reader to have a strong mathematical background * Illustrated throughout with figures and tables Stability and Control of Aircraft Systems provides both the seasoned engineer and the graduate with the know-how necessary to minimize problems with fielded systems in the area of operational performance.